OCT-NIRS Imaging for Detection of Coronary Plaque Structure and Vulnerability - Muller, James; Madder, Ryan (Frontiers in Cardiovascular Medicine, 2020)
A combination optical coherence tomography and near-infrared spectroscopy (OCT-NIRS) coronary imaging system is being developed to improve the care of coronary patients. While stenting has improved, complications continue to occur at the stented site and new events are caused by unrecognized vulnerable plaques. An OCT-NIRS device has potential to improve secondary prevention by optimizing stenting and by identifying vulnerable patients and vulnerable plaques. OCT is already in widespread use world-wide to optimize coronary artery stenting. It provides automated lumen detection and can identify features of coronary plaques not accurately identified by angiography or intravascular ultrasound. The ILUMIEN IV study, to be completed in 2022, will determine if OCT-guided stenting will yield better clinical outcomes than angiographic guidance alone. While the superb spatial resolution of OCT enables the identification of many plaque structural features, the detection by OCT of lipids, an important component of vulnerable plaques, is limited by suboptimal specificity and interobserver agreement. In contrast, NIRS has been extensively validated for lipid-rich plaque detection against the gold-standard of histology and is the only FDA-approved method to identify coronary lipids. Studies in patients have demonstrated that NIRS detects lipid in culprit lesions causing coronary events. In 2019, the positive results of the prospective Lipid-Rich Plaque Study led to FDA approval of NIRS for detection of high-risk plaques and patients. The complementarity of OCT for plaque structure and NIRS for plaque composition led to the sequential performance of NIRS and OCT imaging in patients. NIRS identified lipid while OCT determined the thickness of the cap over the lipid pool. The positive results obtained with OCT and NIRS imaging led to development of a prototype combined OCT-NIRS catheter that can provide co-registered OCT and NIRS data in a single pullback. The data will provide structural and chemical information likely to improve stenting and deliver more accurate identification of vulnerable plaques and vulnerable patients. More precise diagnosis will then lead to OCT-NIRS guided treatment trials to improve secondary prevention. Success in secondary prevention will then facilitate development of improved primary prevention with invasive imaging and effective treatment of patients identified by non-invasive methods.